Odpowiedź :
(19/3*2/19-24/5:6/5):2/5 licznik
25/6*(-3/25)-7/2
(2/3-24/5*5/6)*5/2 licznik
-1/2-7/2 mianownik
(2/3-4/1)*5/2 licznik
-8/2 mianownik
(2/3-12/3)*5/2 licznik
-4 mianownik
-10/3*5/2 licznik
-4 mianownik
-25/3 licznik
-4 mianownik
-25/3:(-4/1) = -25/3*(-1/4)=25/12=2 i 1/12
25/6*(-3/25)-7/2
(2/3-24/5*5/6)*5/2 licznik
-1/2-7/2 mianownik
(2/3-4/1)*5/2 licznik
-8/2 mianownik
(2/3-12/3)*5/2 licznik
-4 mianownik
-10/3*5/2 licznik
-4 mianownik
-25/3 licznik
-4 mianownik
-25/3:(-4/1) = -25/3*(-1/4)=25/12=2 i 1/12